Developing of Monopoly Game Education Media: for Increase The Result of Social Science in Elementary School - Ashari, Eko Purwanti, Putriana Bunga (Universitas Negeri Semarang, 2017)
The results of Kemendikbud (2014) revealed that there were problems in social science learning in elementary school so thatthere are still many students who have not reached the Minimum Score criteria determined. The problem also occured in SDNPakintelan 01, that, social science learning was not optimal in using supporting media, so students did not find their ownknowledge and social science learning outcome is still low which needs a solution to develop media in social science learning.This study aims to determine the effectiveness of monopoly game in improving social science learning outcomes.The researchmethod is Research and Development with the population of this research is all students of grade V SDN Larasati and thesamples are the students of grade V of SDN Pakintelan 01, SDN Pakintelan 03, and SDN Plalangan 04. Expert assessmentresult shows that the monopoly game deserves by media experts and material experts with a percentage of media eligibilityassessment of 92.8% including very feasible criteria, material feasibility assessment of 91.6% including very feasible criteria.Monopoly game influenced cognitive outcomes as evidenced by the average difference of students' ability through the t test of7.340 and the average increase atau N-gain of 0.46 with medium criteria.The conclusion of this research is a monopoly gameworthy and effective used to improve the learning outcomes of social science of grade V elementary school especially historyof Indonesia's struggle against invaders.